Bullying Victimization, Perpetration and Bystander Experiences of Learners in San Guillermo National High School - Samson Jr., Ernesto M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This research outlined the situation regarding bullying victimization, perpetration, and bystander experiences among students at San Guillermo National High School for the academic year 2022 – 2023. This study employed a quantitative approach. A probability sampling method was utilized to identify the sample. The respondents' views on bullying were assessed based on their profile variables. A majority of those surveyed are women. The average age of those surveyed is 16.11. Eighth grade has the highest number of participants. Most of the respondents faced bullying (victims). The majority of them observed other students experiencing bullying (bystanders). Fewer respondents have become bullies towards other learners (bullies). Most bullying incidents occur in homeroom classes. Bullies usually target their peers. The reasons for it lie in physical attributes. Most of the time, the parents and the school are unaware of the bullying incidents. A notable disparity exists in how respondents perceive things when categorized by gender and grade level. The perceptions of the respondents show no significant differences when categorized by age. It is hence advised to educate teachers, students, and parents regarding Republic Act No. 10627, referred to as “The Anti-Bullying Act of 2013,” and DepEd Order No. 40, series of 2012, known as the “DepEd Child Protection Policy.” Developing an Intervention Program to tackle bullying events in schools is essential as well.